A Market-Based Study of the Cost of Default - Davydenko, Sergei A.; Strebulaev, Ilya A.; Zhao, Xiaofei (Review of Financial Studies, 2012)
[This article proposes a novel method of extracting the cost of default from the change in the market value of a firm's assets upon default. Using a large sample of firms with observed prices of debt and equity that defaulted over fourteen years, we estimate the cost of default for an average defaulting firm to be 21.7% of the market value of assets. The costs vary from 14.7% for bond renegotiations to 30.5% for bankruptcies, and are substantially higher for investment-grade firms (28.8%) than for highly levered bond issuers (20.2%), which extant estimates are based on exclusively.]